Coexisting portal vein thrombosis and aortic thrombosis in a patient with COVID-19: A case report and literature review. (2022) - Akella, Ramya; Raj, Rishi; Kannan, Lakshmi; Jacob, Aasems
Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic has rapidly progressed, resulting in significant global morbidity and mortality. Predominantly affecting the respiratory tract, it has been found to be associated with extrapulmonary manifestations such as coagulopathies. We hereby report a case of an elderly man with no predisposing risk factors or history of hypercoagulable disorder who presented with acute onset abdominal pain and was diagnosed with portal vein thrombosis and splenic infarct two weeks following mild COVID-19. Incidentally, the patient was also noted to have aortic thrombosis. The patient was treated with therapeutic anticoagulation with complete resolution in his symptoms. Our case highlights a high risk of coagulopathy following infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).